Synthesis and Degradation of Vinyl Polymers with Evenly Distributed Thioacetal Bonds in Main Chains: Cationic DT Copolymerization of Vinyl Ethers and Cyclic Thioacetals. Issue 4 (7th December 2022) - Uchiyama, Mineto; Murakami, Yukihiro; Satoh, Kotaro; Kamigaito, Masami
Abstract: We report a novel method to synthesize degradable poly(vinyl ether)s with cleavable thioacetal bonds periodically arranged in the main chains using controlled cationic copolymerization of vinyl ethers with a 7‐membered cyclic thioacetal (7‐CTA ) via degenerative chain transfer (DT) to the internal thioacetal bonds. The thioacetal bonds, which are introduced into the main chain by cationic ring‐opening copolymerization of 7‐CTA with vinyl ethers, serve as in‐chain dormant species to allow homogeneous propagation of vinyl ethers for all internal segments to afford copolymers with controlled overall and segmental molecular weights. The obtained polymers can be degraded into low‐ and controlled‐molecular‐weight polymers with narrow molecular weight distributions via hydrolysis. Various vinyl ethers with hydrophobic, hydrophilic, and functional pendants are available. Finally, one‐pot synthesis of multiblock copolymers and their degradation into diblock copolymers are also achieved. Abstract : Degradable poly(vinyl ether)s were synthesized with periodically arranged in‐chain thioacetal bonds via cationic degenerative chain‐transfer copolymerization of vinyl ethers with a 7‐membered cyclic thioacetal. The copolymers can be degraded into low‐ and controlled‐molecular‐weight polymers via hydrolysis. One‐pot synthesis of multiblock copolymers and their degradation into diblock copolymers is also achieved.